HOSPITAL STRATEGY PLANNING USING IFAS AND EFAS BASED SWOT ANALYSIS AT ABC KAMPAR MATERNITY HOSPITAL - Amalia, Rosi; Herniwanti, Herniwanti; Rahmi, Sherly Firta (HEARTY, 2026)
This study aims to analyze the strategic planning of ABC Kampar Mother and Child Hospital (RSIA) using the SWOT analysis approach. The research employed a qualitative method, with data collected through in-depth interviews and questionnaires administered to hospital leaders and managerial staff. The identified internal and external strategic factors were analyzed using the Internal Factors Analysis Summary (IFAS) and External Factors Analysis Summary (EFAS) matrices to determine the hospital’s strategic position. The IFAS analysis shows a total strength score of 45 and a weakness score of 43, resulting in an S − W value of +2, which indicates a relatively strong internal condition. Meanwhile, the EFAS analysis reveals a total opportunity score of 42 and a threat score of 44, producing an O − T value of −2, indicating that the hospital’s external environment is dominated by threats. Based on these coordinates, RSIA ABC Kampar is positioned in Quadrant II (Strength–Threat), suggesting that the appropriate strategy is to leverage internal strengths to anticipate and minimize the impact of external threats. This study is expected to serve as a reference for hospital management in formulating sustainable development strategies to enhance competitiveness and improve the quality of maternal and child health services.